2011
DOI: 10.1093/comjnl/bxr086
|View full text |Cite
|
Sign up to set email alerts
|

Improved Anonymous Multi-receiver Identity-Based Encryption

Abstract: In 2010, Fan et al. proposed an efficient anonymous multi-receiver identity-based encryption scheme. This scheme allows a sender to send an encrypted message to a set of designated receivers while preserving receiver anonymity. The scheme is highly efficient for each receiver as it requires only two pairing operations. However, we found that the scheme failed to protect receiver anonymity and the security notation for receiver anonymity captures only semantics in the case of a single receiver, but does not for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 18 publications
0
66
0
Order By: Relevance
“…Chien [9] proposed an improved scheme which can achieve the receiver's anonymity and enhance the security of the message. However, in encryption phase, this scheme requires a number of bilinear pairing operations which is proportional to the number of receivers.…”
Section: Wireless Communications and Mobile Computingmentioning
confidence: 99%
See 2 more Smart Citations
“…Chien [9] proposed an improved scheme which can achieve the receiver's anonymity and enhance the security of the message. However, in encryption phase, this scheme requires a number of bilinear pairing operations which is proportional to the number of receivers.…”
Section: Wireless Communications and Mobile Computingmentioning
confidence: 99%
“…In Section 4, we first give the correctness analysis of our scheme, and then we compare security and computational cost with the previous literatures [5,6,8,9].…”
Section: Security and Performance Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve preserving privacy of receivers, in 2010, Fan et al [20] presented a new ID-based MRE scheme and claimed that it can protect receiver anonymity; the scheme is highly efficient for each receiver as it requires only two pairing operations. In 2012, Chien [21] found that the scheme of Fan et al [20] failed to protect receiver anonymity and proposed an improved scheme which proves that the scheme enhances security and protects the anonymity of recipients. It is very unfortunate that Wang [22] pointed out the fact that Chien's scheme does not satisfy the indiscernibility of encryption under selective multi-identity, chosen ciphertext attacks.…”
Section: Introductionmentioning
confidence: 99%
“…It is very unfortunate that Wang [22] pointed out the fact that Chien's scheme does not satisfy the indiscernibility of encryption under selective multi-identity, chosen ciphertext attacks. In 2015, Zhang [23] proposed the most efficient anonymous MRIBE scheme in terms of computational cost and communication overhead, compared with schemes of [20][21][22].…”
Section: Introductionmentioning
confidence: 99%